Characterization of biomimetic silicate- and strontium-containing hydroxyapatite microparticles embedded in biodegradable electrospun polycaprolactone scaffolds for bone regeneration. (April 2019) - Surmenev, Roman A.; Shkarina, Svetlana; Syromotina, Dina S.; Melnik, Elizaveta V.; Shkarin, Roman; Selezneva, Irina I.; Ermakov, Artem M.; Ivlev, Sergei I.; Cecilia, Angelica; Weinhardt, Venera; Baumbach, Tilo; Rijavec, Tomaž; et al.
Graphical abstract: Highlights: Hybrid scaffolds of polycaprolactone with modified hydroxyapatite (HA) were prepared. Scaffolds were evaluated via synchrotron radiation–based microcomputed laminography. Scaffolds with Sr-containing HA increased the expression of collagen I and CD34 . Scaffolds with Sr-containing HA facilitated cell mineralization via osteocalcin production. Scaffolds with silicate- and Sr-containing HA microparticles exerted antibacterial activity. Abstract: A significant need exists today to develop novel alternatives to traditional bone grafts. Here, we report the potential use of mechanochemically synthesized hydroxyapatite (HA), silicate-, or strontium-containing HA microparticles and microparticle aggregates in combination with polycaprolactone (PCL) as hybrid scaffolds for filling bone defects. The detailed characterization of scaffolds was performed with high-resolution synchrotron radiation–based microcomputed laminography, XRD, EDX, and FTIR. An in vitro cell-scaffold interaction analysis showed a significant improvement of cell spreading in the case of hybrid scaffolds with silicate- and Sr-containing HA. Scaffolds with Sr- and silicate-containing HA affected the expression of several genes involved in morphogenesis and transcription. Scaffolds with Sr-containing HA increased the expression of markers of the primary component of the extracellular matrix, and scaffolds with Sr-containing HA facilitated cell mineralization via an increase in osteocalcin production. The hybrid scaffolds with silicate- and Sr-containing HA microparticles exerted the highest antibacterial activity against gram-positive bacterium Staphylococcus aureus compared to the unmodified PCL scaffolds. Based on these findings, the obtained scaffolds with Sr- or silicate-containing HA are believed to hold promise for bone tissue regeneration as compared to scaffolds containing pure HA.